Nonalcoholic Steatohepatitis Is Associated With Liver‐Related Outcomes and All‐Cause Mortality in Chronic Hepatitis B. Issue 2 (17th October 2019) - Choi, Hannah S.J.; Brouwer, Willem P.; Zanjir, Wayel M.R.; de Man, Robert A.; Feld, Jordan J.; Hansen, Bettina E.; Janssen, Harry L.A.; Patel, Keyur
Abstract : Background and Aims: Chronic hepatitis B (CHB) and nonalcoholic fatty liver disease are increasingly observed together in clinical practice, and development of nonalcoholic steatohepatitis (NASH) represents another leading cause of liver‐related morbidity and mortality. Our aims were to determine whether biopsy‐proven NASH impacts clinical outcomes in CHB patients and assess prognostic risk factors. Approach and Results: CHB patients attending two tertiary centers in North America and Europe over 13 years with available clinical and biopsy data were included. Patients were categorized as no‐NASH or probable/definite NASH based on standardized histological assessment. Clinical events (death, decompensation, transplant, and hepatoma) were evaluated, and Kaplan‐Meier survival estimates and Cox proportional hazards regression were used to analyze the incidence of events. There were 1, 089 CHB patients, classified as no‐NASH (n = 904, 83%) or NASH (n = 185, 17%), with 52 (6%) versus 27 (15%) experiencing outcome events during follow‐up, respectively. In the multivariable analysis adjusting for age, sex, hepatitis B e antigen serostatus, and diabetes, the presence of NASH and concomitant advanced fibrosis (AF) was significantly associated with clinical outcomes (hazard ratio [95% confidence interval], 4.8 [2.6‐9.0], P   <  0.01) when compared to absence of NASH and AF (reference). NASH and AF were associated with a greater risk of outcomes compared to AF ( P  = 0.01) or NASH alone ( P   <  0.01). Of the three histological determinants of NASH, ballooning and inflammation, but not steatosis, were independently associated with clinical outcomes ( P   <  0.05) in place of NASH. NASH was significantly associated with increased risk of hepatocellular carcinoma and death ( P   <  0.01) but not decompensation ( P  = 0.33). Conclusions: In our large combined tertiary center cohort, patients with concomitant NASH and CHB had more AF and shorter time to development of liver‐related outcomes or death compared to patients with CHB alone. Among patients with AF, superimposed NASH predicted poorer clinical outcomes.